RETRACTED: Foreign inflows, commercial law, and dutch disease: Evidence from developing economies - Guo, Qiaoyun; Chen, Jie; Xiao, He; Mouneer, Salma (Frontiers in Environmental Science, 2022)
It is commonly believed that developing markets require inflows of foreign capital to achieve their growth targets; however, recent research has shown that these inflows are either ineffective or even harmful to the economy. A surge in foreign inflows, such as foreign aid, remittances, and foreign direct investment, into developing markets, particularly, have been connected to the Dutch disease hypothesis. A sharp rise in such inflows will stimulate real exchange rate in receiving nations due to the uptick in the non-tradable sector and the downturn in the tradable sector. The purpose of this research is to investigate, using quantitative approaches, the variations of real exchange rate adjustments that occur in response to official development assistance, foreign direct investments, and international remittances flowing into developing markets. To investigate the onset of Dutch Disease over the period 2001-2020, this analysis makes use of panel data estimation techniques in the form of fixed and random effect models The findings of a substantial amount of econometric investigation revealed that Dutch Disease is present in developing countries. The scope of the study has been broadened to include an investigation of the expansion of both tradable and non-tradable industries. According to the findings of this study, larger inflows of foreign capital slow growth in the tradable sector (the industrial sector), while simultaneously boosting growth in the non-tradable sector (Service sector).